Боротьба запорозьких козаків за збереження своїх вольностей напередодні ліквідації Запорозької Січі (1770-1775 рр.). (Zaporizhzhia Historical Review, 2021)
The article explores the events before Zaporizka Sich liquidation. The author shows that Zaporizhzhyan cossacks struggled actively for their rights and liberties, causing numerous conflicts with the Russian administration.